K. I. CHUKOVSKY-TRANSLATOR: A PORTRAIT AND A SELF-PORTRAIT IN THE METATEXT - A. A. Agajanjan (Гуманитарные и юридические исследования)
Among numerous creative achievements of the outstanding master of the Russian word K.I. Chukovsky the important place is taken by his work «Translation art» («High art»). In the field of the translation he is known as a translator whose main principle of speech activity was the vitalism - following the internal dialogue of two languages and cultures standing behind them when a translator manages to harmonize this interaction and to find communicative consensus. In translation process K.I. Chukovsky was the master of semantic nuances which was due to deep understanding of individual style of the source text author.